"Design thinking" in media management education - A practical hands-on approach - Lugmayr, Artur; Jalonen, M.; Zou, Y.; Libin, L.; Anzenhofer, S. (International Ambient Media Association (iAMEA), 2011)
Within the scope of this paper, we describe a practical hands-on approach of applying "Design Thinking" as principal teaching method for a university course. The course was established as part of the media management minor at the EMMi Lab., at the Tampere Univ. of Technology. The course was held in cooperation with the Tampere University (UTA), and the Tampere University of Applied Sciences (TAMK) at the premises of the New Factory (Demola), an innovation facility in Tampere, Finland. It shall train students in the development of innovations in the media field, and foster creative thinking methods. We discuss the basic curriculum, course structure, methods utilized in the course, as well as we present a reflection on the course in the discussion section. Copyright © (2011) by International Ambient Media Association (iAMEA).